(untitled) (Orfeu, 2021)
This paper is focused on the study of musical dialogues between Brazilian composer Pixinguinha and Argentinian musicians in the decade of 1920. It is based on recent research (BESSA, 2005; MENEZES BASTOS, 2005, COELHO, 2009) that tries to investigate Pixinguinha´s career and contributions through a transnational perspective, stressing international musical influences in his music trajectory. The paper is organized in two parts. The first one is focused on the analysis of the tango La Brisa, written by Uruguaian/Argentinian composer Francisco Canaro. La Brisa was recorded in 1922 by Pixinguinha and his group, and my aim here is to stablish a comparative analysis between this specific recording and Argentinians recordings from the same period made by interpreters such as Carlos Gardel and Orquestra Típica Andreoni. The second part is dedicated to the study of Pixinguinha´s relations with Orquestra Andreoni, a typical tango orchestra that had an intensive musical activity in Rio de Janeiro in 1928. Based on these two case-studies, this paper seeks to shed new lights on historical recordings that shows international influences and musical dialogues in Pixinguinha´s musical career.